1997
DOI: 10.1080/13548509708400578
|View full text |Cite
|
Sign up to set email alerts
|

The role of coping in adjustment to multiple sclerosis-related adaptive demands

Abstract: In general, coping research has faded to examine coping and spec@ illness-related stressors, and with respect to multiple sclerosis (MS), there is a lack of research into cqping with this disease. In this s t d y , stress and coping theory was used to evaluate the role of appraisal and coping strategies in the adjustment to illness-related stressors in M S patients. A total of 134 M S patients and their carers were interviewed and completed self-administered scales. Predictors included illness, M S problems, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 25 publications
(21 reference statements)
10
65
0
2
Order By: Relevance
“…For example, Jean et al [10] found that persons with MS who used more emotion-focused coping strategies (e.g., denial, hoping the problem would just go away) were more likely to experience psychological distress than those who used problem-focused coping strategies (e.g., developing strategies to deal with the situation). Similar results were obtained by both Pakenham [11] and Pakenham et al [12]. Furthermore, Hicky and Greene [13] indicated that these findings applied for both men and women with MS. After an exacerbation of an illness, it would be expected from Folkman and Lazarus' [14] theory that the person would experience this as an uncontrollable event and so be more likely to utilize emotion-focused coping, as opposed to problem-focused coping.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, Jean et al [10] found that persons with MS who used more emotion-focused coping strategies (e.g., denial, hoping the problem would just go away) were more likely to experience psychological distress than those who used problem-focused coping strategies (e.g., developing strategies to deal with the situation). Similar results were obtained by both Pakenham [11] and Pakenham et al [12]. Furthermore, Hicky and Greene [13] indicated that these findings applied for both men and women with MS. After an exacerbation of an illness, it would be expected from Folkman and Lazarus' [14] theory that the person would experience this as an uncontrollable event and so be more likely to utilize emotion-focused coping, as opposed to problem-focused coping.…”
Section: Introductionsupporting
confidence: 90%
“…Particularly for the exacerbation group, it was expected that the coping strategies adopted by respondents would predict mood and self-esteem over time. Most previous studies have examined the cross-sectional relationships between coping and adjustment, and so the level of stability in the adjustment variable could not be partialled out in the analyses [10,12]. However, Pakenham [11] did find that better psychological adjustment over a 12-month period among persons with MS was predicted by high levels of problem-focused coping and low levels of emotionfocused coping at Time 1.…”
Section: Discussionmentioning
confidence: 85%
“…In cross-sectional surveys, emotion-focused coping has been related to lower self-esteem [41], global distress [42][43][44], and depression [13,15,[45][46]. Similar results were found in studies that examined the relationship between coping styles and depression over time [47][48].…”
Section: Copingsupporting
confidence: 66%
“…Consistent with research from other chronic illnesses, both cross-sectional and longitudinal studies in MS have found that passive, avoidant, emotion-focused coping strategies (e.g., wishful thinking, self-blame, avoidance) are related to poorer adjustment and lower levels of QOL (Aikens et al, 1997;Buelow, 1991;Mohr et al, 1997a;O'Brien, 1993b;Pakenham, 1999;Pakenham et al, 1997).…”
Section: Emotion-focused Copingmentioning
confidence: 87%